2019
DOI: 10.3324/haematol.2019.224899
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor 1-mediated iron uptake plays an essential role in hematopoiesis

Abstract: Transferrin receptor 1 (Tfr1) mediates the endocytosis of diferric transferrin in order to transport iron, and Tfr1 has been suggested to play an important role in hematopoiesis. To study the role of Tfr1 in hematopoiesis, we generated hematopoietic stem cell (HSC) specific Tfr1 knockout mice. We found that Tfr1 conditional knockout mice reached full term but died within one week of birth. Further analyses revealed that Tfr1 -deficient HSC had impaired development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…To examine the role of hepatic Trf in the development of proerythroblasts into mature red blood cells, flow cytometry was performed by using the erythroid lineage markers Ter119 and CD44. 27 We found that the cell number of polychromatophilic erythroblasts (R3) increased significantly, whereas orthochromatophilic erythroblasts (R4) and mature erythrocytes (R5) were significantly decreased in the bone marrow of Trf-LKO mice compared with control mice (supplemental Figure 2C). The reticulocyte count decreased in the bone marrow and increased in the circulation, which is consistent with normal compensatory responses to release reticulocytes into the circulation earlier in conditions of more severe anemia.…”
Section: Trf-lko Mice Have Impaired Erythropoiesis and Altered Iron Mmentioning
confidence: 80%
“…To examine the role of hepatic Trf in the development of proerythroblasts into mature red blood cells, flow cytometry was performed by using the erythroid lineage markers Ter119 and CD44. 27 We found that the cell number of polychromatophilic erythroblasts (R3) increased significantly, whereas orthochromatophilic erythroblasts (R4) and mature erythrocytes (R5) were significantly decreased in the bone marrow of Trf-LKO mice compared with control mice (supplemental Figure 2C). The reticulocyte count decreased in the bone marrow and increased in the circulation, which is consistent with normal compensatory responses to release reticulocytes into the circulation earlier in conditions of more severe anemia.…”
Section: Trf-lko Mice Have Impaired Erythropoiesis and Altered Iron Mmentioning
confidence: 80%
“…Multiple studies have shown that Tfr1 deficiency results in functional disorder and even lethality. Mice with Tfr1 conditional knockout in haematopoietic stem cells died within 1 week after birth 23 . Our previous study demonstrated that Tfr1 regulates adipocyte thermogenesis and cell fate determination 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Iron is crucial for normal hematopoiesis since TFR1 inhibition and subsequent iron depletion impair the proliferation and differentiation of hematopoietic precursor cells, and reduce the regeneration potential of hematopoietic stem cells (HSCs) (20). Notably however, excess iron and ROS catalytic production also promote the malignant transformation of HSCs through nicotinamide adenine dinucleotide phosphate oxidases (NOX) and the subsequent depletion of glutathione (GSH) (21).…”
Section: Iron and Acute Myeloid Leukemiamentioning
confidence: 99%